Chronic cavitary pulmonary aspergillosis in an immunocompetent child - Adeyinka A. Davies; Ireti A. Adegbite; Patricia E. Akintan; Usman O. Ibrahim; Abiola O. Adekoya; Rita O. Oladele (Medical Mycology Case Reports, 2022)
Chronic pulmonary aspergillosis (CPA) is a progressive and destructive disease of the lung parenchyma. We report a 9-year-old boy diagnosed with CPA with a positive Aspergillus IgG and chest imaging of cavitary lung lesions. He was treated with oral Itraconazole with significant improvement. This shows that an index of suspicion should be heightened in the paediatric population with cavitary lung lesions because not all cavitary lung lesions are caused by Mycobacterium tuberculosis.